Strategic Management Accounting Practices and Their Impact on Organizational Sustainability - Furqan Doğan (PT. BATARI EDU CALYA, 2026)
This study investigates the relationship between strategic management accounting (SMA) practices and organizational sustainability performance within the Turkish business context. As organizations increasingly face pressure to balance economic profitability with environmental stewardship and social responsibility, understanding how strategic accounting practices contribute to sustainability outcomes becomes critically important. Employing a mixed-methods approach combining content analysis with quantitative performance measurement techniques including entropy-based weighting and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution), this research examines how Turkish organizations integrate sustainability considerations into their strategic management accounting frameworks. The findings reveal that organizations demonstrating higher levels of SMA adoption exhibit superior multidimensional sustainability performance across economic, environmental, social, and governance dimensions. The study contributes to the growing body of literature on sustainability management accounting by providing empirical evidence from an emerging market context, demonstrating that strategic accounting practices serve as critical enablers for achieving balanced sustainability outcomes. The results indicate significant positive relationships between comprehensive sustainability reporting practices and organizational performance, though the value relevance of sustainability efforts remains context-dependent. These findings have important implications for practitioners seeking to leverage management accounting tools for sustainability enhancement and for policymakers developing frameworks to promote corporate sustainability in Turkey.